Training on Separation of Organic and Inorganic Waste in Blimbing Village, Paciran Lamongan District - Rofiatun Solekha; Nynda Ayu Nadira Savitri; Karin Alifia Rachmadani; Badriatul Musyarofah; aisyah hadi ramadani (Utan Kayu Publishing, 2023)
Waste problems are becoming increasingly complex due to the lack of waste processing facilities, low public knowledge about waste management, and the rapid population growth in Paciran District, Lamongan Regency. This activity is carried out with the aim of utilizing it by sorting waste and processing it so that it can produce products. Trash that is scattered on the road is generally due to the low awareness of the surrounding community to dispose of waste in its place. Community service activities are carried out by socialization and training. The socialization carried out is to provide counseling to the community about how to dispose of waste and sorting household waste. Training was conducted for TPS3R officers on how to sort and use them. Organic waste obtained from food scraps is used as maggot feed, while inorganic waste is sold to collectors so that it can increase people's income in the Blimbing village. Apart from that, this activity also produced a BSF (Black Soldier Fly) installation, which is a place for maggot cultivation. It is hoped that in the future this community service activity can be carried out in a sustainable manner, so that the waste in the Blimbing sub-district can be utilized into something of economic value.